STUDENTS'S INTENTION TO USE EMOTION-AWARE VIRTUAL LEARNING ENVIRONMENT: DOES A LECTURER'S INTERACTION MAKE A DIFFERENCE? (Malaysian Journal of Learning and Instruction, 2021)
Purpose: This study explored studentsâ€™ perspective of using emotion-aware Vertual Learning Environment (VLE) in Malaysiaâ€™s higher education institutions. The purpose is to investigate the relationships among dimensions of Technology Readiness Index (TRI), attitude, intention to use VLE, and lecturer interaction. The outcomes concerned the emotions involved in the educational process of Malaysiaâ€™s higher education institutions.Methodology: Quantitative data were collected via an online survey from 260 students. An empirical analysis was then conducted using structural equation modelling (Smart PLS) in two phases: (1) examining the direct effect of studentsâ€™ attitude on VLE adoption intention and (2) examining the indirect effect of constructs using lecturer interaction as a mediator.Findings: The findings revealed a significant mediating role of lecturer interaction on the relationship between attitude and intention to use VLE across the student cohort. Inhibitors, such as insecurity and discomfort, were less significant in affecting studentsâ€™ attitude towards emotion-aware VLE. The results indicate that students are motivated to use VLE when lecturers understand their emotions and react accordingly.Significance: This is one of the studies pertaining to emotions in VLE and lecturer interaction in higher education institutions. The results facilitate an understanding of the pedagogical role of lecturer interaction as a practical learning motivation. It is of particular interest to curriculum and e-learning stakeholders looking to improve studentsâ€™ interactions with the VLE systems. Apart from extending the current literature, this study has significant practical implications for education management in higher learning institutions.